Legal Analysis on the Unilateral Withdrawal from International Trade Treaties in Indonesia - Sefriani, Sefriani (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
In order to boost economic development, the Indonesian government adopted law no. 7/2014 on trade. Under article 85 of the new law, that Indonesian Government has a right to withdraw from international trade treaties it ratified earlier on the basis of national interest. This study is questioning whether this unilateral withdrawal based on considerations of national interests as stipulated in article 85 of law no. 7/2004 can be justified under the 1969 Vienna Convention on the Law of Treaties (VCLT). The study concludes that the unilateral withdrawal from international trade treaties could only be justified if the given treaty provides the so-called ‘exit clause’, a clause that sets out a mechanism for signatory parties who wish to quit the already signed treaty. This clause is also part of the international usages, i.e. under the Lisbon Treaty that gives an opportunity to the Member States to quit the EU following special procedural rules. In addition to that, in case the ratified treaty does not contain an exit clause, considerations of national interest can only be used in accordance with article 46 and 62 of the VCLT.